SOME NOTES ON MADRASAH EDUCATION IN BANGLADESH: A HISTORICAL DESCRIPTION - Karim, M Abdul (IJISH (International Journal of Islamic Studies and Humanities), 2018)
This paper tries to describe a historical development on Madrasah education system in Bangladesh. Bangladesh or formerly known as Eats Pakistan has significant contribution in spreading Islam in Asia. In education level, this major role played by thousands of Madrasah (state or private) in Bangladesh. While some people argued that the alumni of the Madrasah are inferior to the alumni of Western education institutions, the history proved that the alumni of Madrasah have substantial contribution in creating Muslim scholars not only expertise in religious teaching but also in secular sciences. This analysis also expected to be a role model in comparing Madrasah education system in Indonesia.